2015
DOI: 10.3892/ijmm.2015.2276
|View full text |Cite
|
Sign up to set email alerts
|

PLIN2 inhibits insulin-induced glucose uptake in myoblasts through the activation of the NLRP3 inflammasome

Abstract: Abstract. Impaired lipid metabolism and inflammatory pathways have individually been implicated in the development of insulin resistance in skeletal muscle; however, little evidence is available to date linking the two in this context. In this study, we explored a potential molecular mechanism underlying insulin resistance in myoblasts mediated by the crosstalk between lipid accumulation and inflammatory pathways. We examined the influence of perilipin 2 (PLIN2), one of the most highly expressed lipid droplet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…We previously reported that excessive lipid accumulation within skeletal muscle cells as a result of overexpressing lipid droplets induces IL‐1β production via activation of the NLRP3 inflammasome pathway 15. Thus, we speculated that exogenous treatment with PA might also stimulate IL‐1β secretion by C2C12 myotubes.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We previously reported that excessive lipid accumulation within skeletal muscle cells as a result of overexpressing lipid droplets induces IL‐1β production via activation of the NLRP3 inflammasome pathway 15. Thus, we speculated that exogenous treatment with PA might also stimulate IL‐1β secretion by C2C12 myotubes.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, we speculated that skeletal muscle cells could produce pro‐inflammatory mediators in response to PA. Previously, we found that C2C12 myoblasts produce IL‐1β following the accumulation of intracellular lipids by increasing lipid droplets within the cells 15. Therefore, we hypothesized that C2C12 myotubes were capable of producing IL‐1β following exposure to PA because FFAs cause intracellular lipid accumulation.…”
Section: Discussionmentioning
confidence: 92%
“…SAA1 induces IL-1β expression [46] and secretion [47] and activates the Nlrp3 inflammasome in immune cells [46]. The Nlrp3 inflammasome is contained and active in C2C12 myocytes [48] . IL-1β induces atrogene expression in myocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, also, resistin has been shown to promote IMCL storage in primary human myotubes . Importantly, increased IMCL storage results in the accumulation and dysregulation of detrimental lipid intermediates such as diacylglycerols (DAGs) and ceramides, and those intermediates lead to insulin resistance through activation of protein kinase C (PKC) . High levels of DAG and ceramides have also been suggested to play a role in the development of muscle loss .…”
Section: Determinants Of Muscle Massmentioning
confidence: 99%
“…71 Importantly, increased IMCL storage results in the accumulation and dysregulation of detrimental lipid intermediates such as diacylglycerols (DAGs) and ceramides, and those intermediates lead to insulin resistance through activation of protein kinase C (PKC). [90][91][92][93][94][95][96][97][98][99][100] High levels of DAG and ceramides have also been suggested to play a role in the development of muscle loss. 16, [101][102][103] In C2C12 and L6 myotubes, treatment with the fatty acid palmitate induced ceramide accumulation, and this was associated with increased expression of pro-atrophic genes such as atrogin-1/MAFbx, increased levels of FoxO3, upregulated eIF2α phosphorylation, and decreased protein synthesis.…”
Section: Lipid Accumulation In Skeletal Musclementioning
confidence: 99%